ITEM ANALYSIS ON ENGLISH SUMMATIVE TEST AT THE EIGHTH GRADE JUNIOR HIGH SCHOOLS IN PONTIANAK - Manfenrius, Andy; Sutapa, Gatot; Wijaya, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstrac: This research concerns on item analysis, including level of difficulty, discriminating power, and distractor analysis of the English Summative Test Items at the Eighth Grade Junior High School in Pontianak in Academic Year 2014/2015. The purpose is to provide current information about the quality of the English summative test and to compare the quality of the test items at X, Y and Z Junior High School. Some qualitative evidence and quantitative data from the test scores are collected, analysed, and interpreted. For the sample of participants as examinees, 3 junior high schools are selected through stratified purposive sampling based on the similar school accreditation ranks. The item analysis findings show 98% test items at X Junior High School, 94% test items at Y Junior High School, and 100% test items at Z Junior High School that are in need of improvement. The test developers need to consider revising items with very low or very high item difficulty and very low discrimination ability. Furthermore, an action needs to be taken to revise distractors that are not plausible.   Key word: item analysis, summative test, quality of test Abstrak: Penelitian ini mengacu pada analisis soal ulangan umum yang meliputi tingkat kesukaran, daya pembedaan, dan analisis pengecoh kelas 8 SMP di Pontianak tahun ajaran 2014/2015. Penelitian ini bertujuan untuk menyajikan informasi tentang kualitas soal dan perbandingan kualitas soal di SMP X, Y, and Z. Beberapa data kualitatif dan kuantitatif, seperti nilai telah terkumpul, dianalisis, dan diinterpretasikan. Sampel peserta tes dipilih dari 3 sekolah berdasarkan tingkat akreditasi yang sama. Penemuan dari analisis soal ini menunjukkan bahwa sebanyak 98% soal di SMP X, 94% soal di SMP Y, dan 100% soal di SMP X memerlukan peningkatan kualitas. Pembuat soal harus mengubah soal yang terbukti kurang berkualitas. Terakhir, soal-soal yang diubah harus segera ditindak lanjuti.   Kata kunci: analisis soal, soal ulangan umum, kualitas soal